Kron 3: a fourth intermediate age cluster in the SMC with evidence of multiple populations - Hollyhead, Katie; Lardo, C.; Kacharov, Nikolay; Bastian, Nate; Hilker, Michael; Rejkuba, Marina; Koch-Hansen, Andreas; Grebel, Eva K.; Georgiev, Iskren Y. (Monthly notices of the Royal Astronomical Society, 2018)
We present the results of a spectroscopic study of the intermediate age (≈6.5 Gyr) massive cluster Kron 3 in the Small Magellanic Cloud. We measure CN and CH band strengths (at ≃3839 and 4300 Å, respectively) using VLT FORS2 spectra of 16 cluster members and find a sub-population of five stars enriched in nitrogen. We conclude that this is evidence for multiple populations in Kron 3, the fourth intermediate age cluster, after Lindsay 1, NGC 416 and NGC 339 (ages 6-8 Gyr), to display this phenomenon originally thought to be a unique characteristic of old globular clusters. At ≈6.5 Gyr this is one of the youngest clusters with multiple populations, indicating that the mechanism responsible for their onset must operate until a redshift of at least 0.75, much later than the peak of globular cluster formation at redshift ∼3.
Gesehen am 14.03.2018